EVALUATION OF ADVANCED POTATO CLONES FOR DROUGHT TOLERANCE IN ARID ZONE IN RAJASTHAN, INDIA - Sharma, Neeraj; Rawal, Sanjay; Kadian, Mohinder; Arya, Sushma; Bonierbale, Merideth; Singh, B P (Potato Journal, 2015)
Â Â Â